Information systems as supporters of nurses’ work: experiences by system brand - Kyytsönen, Maiju; Hyppönen, Hannele; Koponen, Samuli; Kinnunen, Ulla-Mari; Saranto, Kaija; Kivekäs, Eija; Kaipio, Johanna; Lääveri, Tinja; Heponiemi, Tarja; Vehko, Tuulikki (Finnish Journal of eHealth and eWelfare, 2020)
Information systems are key tools for nursing care. The article examines the extent to which different client information systems and electronic health records support the work of nurses in specific work environments. The aim is to provide information on the achievement of the national strategy for information management and on nurses’ user experiences of individual systems as feedback to the system suppliers. The data collection was carried out as a survey on nurses’ system experiences in the spring of 2020. The survey was answered by 3,912 nurses. Most of the respondents worked in public hospitals, community health centers, social services or private sector. The most commonly used client information systems and electronic health records were in order of frequency: Lifecare, Uranus, Pegasos, Apotti (system brand: Epic), Effica Healthcare, Mediatri, Esko, DynamicHealth and DomaCare. The questions that were reported in the study were related to information systems’ ability to support interaction (4), benefits (4), usability (2), and technical functionality (3) and the use of paper and fax (1), information systems’ evaluation on a numeric scale (1) and direct feedback to system suppliers (30). The survey for nurses was conducted for the second time, so it was possible to examine the changes since 2017. According to the results, it appeared that the information systems’ ability to support work improved or remained unchanged for the most part. The results varied by information system brands and between the work environments as well as between the same brands in different work environments. Nurses appeared to be particularly satisfied with the information systems’ ability to support collaboration and information flow between nurses within their own organization and between nurses and physicians. They also felt that the information systems provided benefits to the care process of clients and patients. On the other hand, the information flow between organizations was still dependent on paper and fax. The respondents also identified more problems than well-functioning features in the information systems. Thus, although the development trend of the information systems appeared to be positive, the information systems did not fully support the work of nurses in all respects. Therefore the systematic monitoring of the information systems is worth continuing.